Solvent mediated inclusion of metal oxide into block copolymer nanopatterns: Mechanism of oxide formation under UV-Ozone treatment. (31st May 2019) - Ghoshal, Tandra; O'Connell, John; Sinturel, Christophe; Andreazza, Pascal; Holmes, Justin D.; Morris, Michael A.
Abstract: Uniform, periodic and ordered iron oxide nanopatterns can be generated by selective metal ion inclusion into microphase separated polystyrene-b-poly(ethylene oxide) (PS-b-PEO) block copolymer (BCP) thin films. After solvent mediated metal ion inclusion into the PEO block, an ultraviolet-ozone (UVO) treatment was used to remove the polymer and oxidize the metallic ions to their oxides. This paper provides an in-depth study of the UVO processing steps as a function of exposure time. Surface wettability, topography, morphology, compositional and interfacial changes were analysed by contact angle measurement, microscopic and spectroscopic techniques through the UVO treatment. It was found that the UVO treatment initially cross-links the polymer network followed by oxidation and removal of the polymer simultaneously. It was also found that if short UVO exposure times are used, a post calcination treatment can be used to generate similar patterns. The iron oxide nanopatterns created due to strong coordination bond between metallic ions and free electron pairs of O atoms in the PEO and these interactions are responsible for the final pattern mimicking the original self-assembled BCP morphology. The film thicknesses, surface roughness, the size/shape of the iron oxides and patterns, the amount of residual polymers were also investigated regarding the UVO exposure time. Graphical abstract: Image 1 Highlights: Mechanism of metal oxide nanopatterns formation by block copolymers under UV-Ozone treatment.